The roles of expected profitability, Tobin's Q and cash flow in econometric models of company investment - Steve Bond; Alexander Klemm; Rain Newton-Smith; Murtaza Syed; Gertjan Vlieghe (Institute for Fiscal Studies (IFS), 2004)
Evidence that cash flow has a significant effect on company investment spending, after controlling for Tobin's average Q, has often been interpreted as suggesting the importance of financing constraints. Recent work on measurement error in the Q model casts doubt on this interpretation. It is possible that the Q model may not be identified if there are \~Nubbles' in stock market valuations that are both persistent over time and that are correlated with fundamental values. Cash flow may then provide additional information about expected profitability that is not captured by a poorly measured Tobin's average Q variable. We explore this hypothesis empirically using UK panel data on companies for which analysts' earnings forecasts are available from the IBES database. The results point to a severe measurement error in average Q. The paper finds that, controlling for expected profitability using analysts' earnings forecasts, cash flow becomes insignificant. Both sales growth and cash-stock variables do provide additional information, which could either be capturing expectations of profitability at longer horizons, or reflect misspecification of the basic Q model. Results for subsamples do not suggest financing constraints as a likely explanation for these findings.
Keywords: 330; Tobin's Q; Investition; Betriebliche Investitionspolitik; Erwartungstheorie; Unternehmenserfolg